Determinan Kualitas Audit pada Inspektorat Daerah Provinsi Sumatera Selatan - Mutiara Az Zahra Tobing; Siska Aprianti; Anggeraini Oktarida (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to determine the effect of Independence, Integrity, Due Professional Care, and Audit Capacity Stress on Audit Quality (Empirical Study on the Regional Inspectorate of South Sumatra Province) in 2024. This research method uses quantitative research using primary data in the form of distributing questionnaires. The population in this study were all auditors who worked at the Regional Inspectorate of South Sumatra Province and the sample obtained by researchers was 32 respondents from a total of 39 questionnaires distributed. The data analysis technique is multiple linear regression analysis with the help of SPSS software version 26. The results show that partially Independence, Integrity, Due Professional Care, and Audit Capacity Stress have a positive and significant effect on Audit Quality. Meanwhile, simultaneously Independence, Integrity, Due Professional Care, and Audit Capacity Stress have a positive and significant effect on Audit Quality at the Regional Inspectorate of South Sumatra Province.